A center-based, ambulatory care concept for hidradenitis suppurativa improves patient outcomes and is also cost-effective - Marcus Heise; Petra Staubach; Georgios Nikolakis; Lukas Schollenberger; Melanie Mauch; Marion Burckhardt; Marina Zamsheva; Alexandra Strobel; Gero Langer; Falk Bechara; Uwe Kirschner; Katharina Hennig; et al. (Journal of Dermatological Treatment, 2023)
AbstractBackground Hidradenitis suppurativa (HS) is a chronic inflammatory skin disease affecting approximately 1% of the population. The patient journey through the German health care system leads to high disease burden and substantial treatment costs. The EsmAiL study showed that an innovative, interprofessional, multimodal care-concept reduces disease activity and burden of HS compared to standard care. This paper examines the costs of treating HS in Germany and compares them with those of the innovative care concept implemented in EsmAiL.Methods EsmAiL was a two-arm, multicenter, prospective randomized controlled trial including 553 adults with HS. The study was registered in the German Clinical Trials Registry (DRKS00022135). The control group (CG) remained in standard care, whereas the intervention group (IG) was referred to specialized so-called ‘acne-inversa-centres (AiZ)’ where patients were treated with a structured, interdisciplinary approach. The present paper analyses the treatment costs for a subpopulation based on health insurance cost data from the two largest German health insurers. Quality-Adjusted Life Years (QALY) was assessed based on Dermatology Life Quality Index (DLQI).Results Total annual treatment costs per patient were €3,966.07 in standard care (n = 89) and €3,974.37 in the innovative care (n = 93). The costs per additional QALY amounted to €12,698.72 in the IG. Given the conventional and established threshold of €22,600 to €33,900 per QALY, the innovative treatment in AiZ proved to be cost-effective.Conclusion Treatment costs of HS are substantial and increase with disease severity. The new form of care is cost-effective and is expected to decrease costs in the long run.